1997
DOI: 10.1128/jb.179.13.4138-4142.1997
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic regulation of the sucABCD genes of Escherichia coli, which encode alpha-ketoglutarate dehydrogenase and succinyl coenzyme A synthetase: roles of ArcA, Fnr, and the upstream sdhCDAB promoter

Abstract: The sucABCD genes of Escherichia coli encode subunits for two enzymes of the tricarboxylic acid (TCA) cycle, ␣-ketoglutarate dehydrogenase (sucAB) and succinyl coenzyme A synthetase (sucCD). To examine how these genes are expressed in response to changes in oxygen and carbon availability, a set of sucA-lacZ, sucC-lacZ, sdhCDAB-sucA-lacZ, and sdhC-lacZ fusions were constructed and analyzed in vivo. While the expression of a sucA-lacZ fusion was low under all cell growth conditions tested, the expression of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 23 publications
6
74
0
Order By: Relevance
“…In the absence of oxygen, the oxygen-sensitive global regulators ArcA and FNR mediate the repression of many TCA promoters, but most dramatically the sdh-suc operon, which encodes SDH, KDGH, and the SCSC (104,105,170,293,335,339,406). The mechanism that causes glucose repression, and thus the Crabtree effect, is less clear.…”
Section: Limiting the Tricarboxylic Acid Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of oxygen, the oxygen-sensitive global regulators ArcA and FNR mediate the repression of many TCA promoters, but most dramatically the sdh-suc operon, which encodes SDH, KDGH, and the SCSC (104,105,170,293,335,339,406). The mechanism that causes glucose repression, and thus the Crabtree effect, is less clear.…”
Section: Limiting the Tricarboxylic Acid Cyclementioning
confidence: 99%
“…A more moderate inhibition occurs in the presence of excess glucose (160,170,193,212,(335)(336)(337)(338)(339)413).…”
Section: Limiting the Tricarboxylic Acid Cyclementioning
confidence: 99%
“…Metabolic enzymes, such as SDH, are tightly regulated so they function only when required (Cecchini et al, 2002;Park et al, 1995Park et al, , 1997. We previously identified SdhE and demonstrated that it is a soluble cytoplasmic protein required for SdhA flavinylation and activation of SDH (McNeil et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This latter enzyme uses phosphate as a substrate to generate ATP (Wanner, 1995). Expression of sucCD is controlled from the sdh promoter (Park et al, 1997). So decreasing sucCD expression, due to substrate (i.e.…”
Section: Discussionmentioning
confidence: 99%